Impact of Antibiotic Stewardship on Treatment of Hospitalized Children with Skin and Soft-Tissue Infections - Giulia Brigadoi; Sara Rossin; Lorenzo Chiusaroli; Giulia Camilla Demarin; Linda Maestri; Francesca Tesser; Martina Matarazzo; Cecilia Liberati; Elisa Barbieri; Carlo Giaquinto; Liviana Da Dalt; Silvia Bressan; et al. (MDPI AG, 2024)
Background: Skin and soft-tissue infections (SSTIs) are common infectious syndromes in children. Overusing broad-spectrum antibiotics has contributed to rising antibiotic resistance, complicating treatment outcomes. To address this issue, antimicrobial stewardship programs (ASPs) have been implemented to optimize antibiotic use. This study evaluated the impact of a multifaceted ASP on antibiotic prescribing practices for SSTIs in a pediatric acute care setting over eight years. Methods: We conducted a quasi-experimental study at the Pediatric Acute Care Unit of the Padua University Hospital, including children admitted with SSTIs from October 2014 to September 2022, to evaluate the impact of a multifaceted ASP implemented in October 2015. The study was divided into three periods: pre-implementation (October 2014-September 2015), post-implementation (October 2015-March 2020), and COVID-19 (April 2020-August 2022). Data on antibiotic prescriptions and microbiological results were collected and analyzed. Results: The implementation of the ASP led to a significant reduction in the use of broad-spectrum antibiotics, particularly third-generation cephalosporins (from 40.4% to 9.8%) and glycopeptides (from 21.1% to 1.6%). There was a notable increase in the prescription of Access antibiotics, from 30% in the pre-implementation to over 60% in the post-implementation and 80% during COVID-19. No increase in the hospital length of stay was observed. Microbiological results showed no significant changes in bacterial profiles over time. Conclusions: The use of the ASP effectively improved antibiotic prescribing practices, reducing reliance on broad-spectrum antibiotics even during the COVID-19 pandemic. These findings highlight the value of ongoing stewardship efforts and suggest the need for similar programs in ambulatory settings to further address antibiotic resistance.